Comparative study of Arduino Types and Raspberry Pi with Programming Languages - Shajan Mohammed Mahdi; Mohanad Ali Meteab Al-Obaidi; Reyadh Hazim Mahdi (Newinera Publisher, 2022)
The world is developing at an amazing speed through modern technologies to control things and microcontrollers have become a preoccupation of most developers of remote and proximity control devices in various industrial, household, and educational sectors, so it is necessary to study them in-depth and know the differences between Arduino and Raspberry in terms of hardware and software so that the developer is aware of what they can use it to build his project. Both Arduino and Raspberry are microcontrollers, but the first works without the need to connect to a computer, and works through an open source program as it is a single board and deals with a simple program every time and can connect to the Internet, while Raspberry connects to a computer via USB It deals with the language of Linux and Ruby and can perform mathematical and arithmetic operations and encrypt Bitcoin currencies, for these reasons, all these concepts will be explained in this paper, and that any technician or programmer can choose the best electronic parts Arduino or Raspberry in order to get the project done better.